2021
DOI: 10.1002/asia.202101156
|View full text |Cite
|
Sign up to set email alerts
|

o‐Cyanobenzoate: A Recyclable and Reusable Stereo‐directing Group for β‐O‐Glycosylation via Pd(0)‐catalyzed Ferrier Rearrangement

Abstract: Inner sphere Tsuji‐Trost reaction has found recent application for β‐selective Ferrier rearrangement of glycal substrates with alcohol nucleophiles. Herein, we report an efficient and stereoselective synthesis of 2,3‐dideoxy‐β‐O‐glycosides from C3‐(o‐cyanobenzoate) ester protected glycal donors via Ferrier rearrangement under Pd(0)‐catalyzed Tsuji‐Trost conditions. The synthesized donors indeed reacted with a variety of acceptors to afford the corresponding glycosides in good yields and excellent β‐stereoselec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In continuation to our efforts to discover sustainable glycosylation methods, 26–29 we have recently reported cyanomethyl ether (CNMe) as a participating group for stereocontrolled trans -1,2-β- O -glycosylation when present at the C2-position of thioglycosides. During our earlier work a facile synthetic method for CNMe ether formation from C2-hydroxy allowed us to circumvent the well-documented difficulties of low yield and conversion associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation to our efforts to discover sustainable glycosylation methods, 26–29 we have recently reported cyanomethyl ether (CNMe) as a participating group for stereocontrolled trans -1,2-β- O -glycosylation when present at the C2-position of thioglycosides. During our earlier work a facile synthetic method for CNMe ether formation from C2-hydroxy allowed us to circumvent the well-documented difficulties of low yield and conversion associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…It was thus concluded that the reaction necessitated coordination of the amide group with the metal center. On the basis of these observations and earlier literature precedence, ,, we propose that amidyl O at the equatorial C3-ester of glycals enables Pd(0) coordination from the β face of substituted glycal I with subsequent π-allyl formation from above the plane of the sugar ring II (Scheme c). An approaching hard alcohol nucleophile coordinates to the hard metal center III followed by syn -facial attack at the C-1 position to afford β- O -glycosides.…”
mentioning
confidence: 99%
“…Conventional Pd(0) co-ordinating groups, ethyl carbonate and picoloyl ester, have thus been reported by Liu’s group as suitable LGs for Ferrier rearrangements of glucal substrates 1 (Figure a). With our continued interest in design and development of efficient synthetic methods in glycochemistry, including stereoselective glycosylations, we have recently reported the β-directing ability of o -cyanobenzoate ( o -CNBz) ester 2 (Figure b). The presence of a nitrile moiety on the Bz ester enabled metal co-ordination for the stereoselective rearrangement, which is in stark contrast to the unreactive nature of the parent benzoate group in the same reaction.…”
mentioning
confidence: 99%